Study on Concrete by Replacing Cement with Red Mud, Fly Ash and Hydrated Lime - Rohit Singh; Afzal Khan (International Journal of Scientific Research in Civil Engineering, 2022)
At global level, red mud (RM) production is rising as a result of the expansion of the aluminum industry. In overall, 0.8 to 1.5 tons of RM can be produced for every ton of alumina produced. Globally, 1.7 billion tons of RM are produced each year due to the aluminum industry’s quick development. Due to the hydroxide (NaOH) injected throughout the production of aluminum, RM typically has a pH between 10.5 to 12.5. In this study, we’re looking at how red mud is used in concrete. Here, we’re making concrete cube and beam samples with red mud added in the recommended weight percentage. and figuring out its tensile, flexural, and compressive strengths. Taking into account various concrete grade levels. The results of this study will support the physical property changes in concrete that were noticed after red mud was added.